Association between sleep-disordered breathing and periodontal diseases: A systematic review protocol - Chen, Danyan; Meng, Ziyan; Zhao, Tingting; Yu, Xueqian; He, Hong; Hua, Fang; Dong, Weili (Frontiers in Medicine, 2022)
Background Sleep-disordered breathing (SDB) is a chronic sleep-related breathing disorder, considered associated with increased risk of cardiovascular disorders, metabolic disorders, cognitive dysfunction and behavior changes. Periodontal diseases are chronic infectious diseases that are also believed to be associated with cardiovascular diseases, metabolic syndrome and cognitive dysfunction. Several studies have indicated that SDB may be associated with periodontal diseases through certain mechanisms such as inflammation response, oxidative stress and oral dryness. The aim of this systematic review is to explore the association between SDB and periodontal diseases in an integrated approach. Materials and Methods This systematic review will include cohort studies, cross-sectional studies and case-control studies that are identified by electronic and manual searches. Electronic searches will be conducted in the following databases: PubMed, Embase, Scopus and Web of Science. Our search will cover articles published from inception of databases to March 2022 without restrictions in language and settings. Pre-determined eligibility criteria include: participants (participants without a history of respiratory diseases, history of periodontal treatment within the past 6 months and history of medication that is known to influence SDB or periodontal diseases); exposure (participants who have been diagnosed with SDB or at high-risk for SDB); comparison (participants without SDB); and outcome (periodontal parameters, such as probing depth, clinical attachment level, bleeding on probing, radiographic bone loss). Two authors will perform study screening and data extraction independently and in duplicate. All discrepancies will be solved by discussion. The methodological quality of included studies will be assessed using the Newcastle-Ottawa Scale. Discussion This systematic review will summarize the existing evidence on the association between SDB and periodontal diseases, a topic of controversy and clinical significance. Its findings can provide evidence for the development of relevant prevention and treatment strategies. The results will be disseminated through peer-reviewed journals. Systematic review registration www.crd.york.ac.uk/PROSPERO, PROSPERO ID: CRD42022313024. Registered on March 28th 2022.